Effect of levosimendan on myocardial contractility, coronary and peripheral blood flow, and arrhythmias during coronary artery ligation and reperfusion in the in vivo pig model. Issue 1 (1st July 2001) - du Toit, E; Hofmann, D; McCarthy, J; Pineda, C
Abstract : OBJECTIVE: To determine whether levosimendan, a calcium sensitiser that facilitates the activation of the contractile apparatus by calcium, improves myocardial contractile function during severe ischaemia and reperfusion without exacerbating the incidence of arrhythmias. DESIGN: Pigs were pretreated orally twice daily for 10 days with 0.08 mg/kg levosimendan or placebo. On day 11 the left main coronary artery was ligated for 30 minutes, followed by 30 minutes of reperfusion. A bolus dose of levosimendan, 11.2 μg/kg intravenously, or placebo was given 30 minutes before coronary ligation, followed by a continuous infusion of 0.2 μg/kg/min levosimendan or placebo for the remainder of the experiment. RESULTS: During the ischaemic period, cardiac output was higher in the levosimendan group than in the placebo group (mean (SD): 2.6 (0.5) v 2.0 (0.2) l/min, p < 0.05) and systemic vascular resistance was lower (2024 (188) v 2669 (424) dyne.s −1 .cm −5, p < 0.005). During reperfusion, cardiac output and contractility (LVmax dP/dt (pos), 956 (118) v 784 (130) mm Hg/s, p < 0.05) were increased by levosimendan. The incidence of ischaemic ventricular fibrillation and tachycardia was similar in the two groups but there were more arrhythmic events (ventricular tachycardia and ventricular fibrillation) in the levosimendan treated group (8/12 levosimendan v 1/9 control p = 0.05). CONCLUSIONS: Levosimendan improved cardiac output and myocardial contractility during coronary artery ligation and reperfusion. However, it increased the number of arrhythmic events during ischaemia in this model of in vivo regional ischaemia.